Toward a Microencapsulated 3D hiPSC-Derived in vitro Cardiac Microtissue for Recapitulation of Human Heart Microenvironment Features - Abecasis, Bernardo; Canhão, Pedro G.M.; Almeida, Henrique V.; Calmeiro, Tomás; Fortunato, Elvira; Gomes-Alves, Patrícia; Serra, Margarida; Alves, Paula M. (Frontiers in Bioengineering and Biotechnology, 2020)
The combination of cardiomyocytes and non-myocyte cardiac populations, such as endothelial cells and mesenchymal cells, has been shown to be critical for recapitulation of the human heart tissue for in vitro cell-based modeling. However, most of the current engineered cardiac microtissues still relying on either: (i) murine/human limited primary cell sources; (ii) animal-derived and undefined hydrogels/matrices with batch-to-batch variability; or (iii) culture systems with low compliance with pharmacological high throughput screenings. In this work, we explored a culture platform based on alginate microencapsulation and suspension culture systems to develop 3D human cardiac microtissues which entails the co-culture of human pluripotent stem cell (hiPSC) cardiac derivatives including aggregates of hiPSC-cardiomyocytes (hiPSC-CM) and single cells of hiPSC-derived endothelial cells and mesenchymal cells (hiPSC-EC+MC). We demonstrate that the 3D human cardiac microtissues can be cultured for 15 days in dynamic conditions while maintaining the viability and phenotype of all cell populations. Noteworthy, we show that hiPSC-EC+MC survival was promoted by the co-culture with hiPSC-CM as compared to the control single cell culture. Additionally, the presence of the hiPSC-EC+MC induced changes in the physical properties of the biomaterial, as observed by an increase in the elastic modulus of the cardiac microtissue when compared to the hiPSC-CM control culture. Detailed characterization of the 3D cardiac microtissues revealed that the crosstalk between hiPSC-CM, hiPSC-EC+MC and extracellular matrix induced the maturation of hiPSC-CM. The cardiac microtissues displayed functional calcium signaling and respond to known cardiotoxins in a dose depend manner. This study is a step forward on the development of novel 3D cardiac microtissues that recapitulate features of the human cardiac microenvironment and is compliant with the larger numbers needed in pre-clinical research for toxicity assessment and disease modelling.